Screening of known disease genes in congenital scoliosis. Issue 6 (9th September 2018) - Takeda, Kazuki; Kou, Ikuyo; Mizumoto, Shuji; Yamada, Shuhei; Kawakami, Noriaki; Nakajima, Masahiro; Otomo, Nao; Ogura, Yoji; Miyake, Noriko; Matsumoto, Naomichi; Kotani, Toshiaki; Sudo, Hideki; et al.
Abstract: Background: Congenital scoliosis (CS) is defined as a lateral curvature of the spine due to the vertebral malformations and has an incidence of 0.5–1/1, 000 births. We previously examined TBX6 in Japanese CS patients and revealed that approximately 10% of CS was caused by TBX6 mutations. However, the genetic cause of remaining CS is unknown. Methods: We recruited 78 CS patients without TBX6 mutations and major comorbidities, and investigated the genes previously reported to be associated with CS and congenital vertebral malformations by whole‐exome sequencing. Results: We identified the compound heterozygous missense variants in LFNG in one patient. No likely disease‐causing variants were identified in other patients, however. LFNG encodes a GlcNAc‐transferase. The LFNG variants showed loss of their enzyme function. Conclusions: A LFNG mutation is reported in a case of spondylocostal dysostosis (SCD), a skeletal dysplasia with severe malformations of vertebra and rib. The CS patient with LFNG mutations had multiple vertebral malformations including hemivertebrae, butterfly vertebrae, and block vertebrae, and rib malformations. LFNG mutations may cause a spectrum of phenotypes including CS and SCD. The current list of known disease genes could explain only a small fraction of genetic cause of CS. Abstract : We previously examined TBX6 in Japanese congenital scoliosis patients and revealed that approximately 10% of CS was caused by TBX6 mutations. We recruited 78 CS patients without TBX6 mutations and investigated the genes previously reported to be associated with CS and congenital vertebral malformations by whole‐exome sequencing. We identified the compound heterozygous missense mutation in LFNG in one patient.